EXPLORING ENGLISH LISTENING PROBLEMS AMONG EFL STUDENTS AT IAIN KUDUS - Azizah Maulina Erzad (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Listening comprehension becomes one of the most difficult skills for most of English learners especially EFL learners. As a foreign language, English is rarely used in communication by EFL learners in their daily life. Therefore, the learners or students always face some difficulties/problems in listening comprehension. It can be seen from the results of their tests. The purpose of this study is to investigate the problems occur in listening class of EFL students at IAIN Kudus and the solutions to overcome those problems. The EFL students in this study refer to the English Education Department students of IAIN Kudus. The participants of this study are the second semester of English Education Department students. This study is a qualitative research. Observation, interview and documentation were conducted to collect the data. By conducting this study, several problems in listening comprehension can be revealed. The listening problems encountered by the EFL students are the pronunciation (accents), speedy delivery and length of the listening, physical conditions, unfamiliar vocabularies and terminologies, and limited facility for listening. Some actions should be done to overcome these obstacles occurred during listening process. The solutions to overcome the problems are students should be focus, practice more in listening English, memorize vocabularies, and prepare a language laboratory.